Molecular dynamics simulation of nickel‐coated graphene bending. (1st February 2018) - Katin, Konstantin P.; Prudkovskiy, Vladimir S.; Maslov, Mikhail M.
Abstract : The work presents a force field molecular dynamics study of nickel‐coated graphene sheet bending at temperatures 300 and 1300 K. Nickel film is represented by nickel atoms located above the centres of carbon hexagons. Parameters for carbon–nickel interaction are fitted with regard to the accurate density functional calculations. Unstrained or flat configuration of the nickel–graphene system is found to be energetically unfavourable for the considered temperatures. Two types of curvatures are taken into account. Positive curvature is characterised by the nickel atoms located closer to the bending axis than the carbon ones, and negative curvature corresponds to the reverse atomic positions. It is found that the equilibrium radius for the curved nickel–graphene complex with the negative curvature is less than the corresponding value for the positive one. However, in both cases the equilibrium curvature radius of nickel‐coated graphene is of the order of several nanometres. It is shown that both temperature and bending directions (zigzag and armchair) weakly affect the bending energy and do not change the equilibrium radius. Bending behaviour of the system is defined by the carbon–nickel interaction rather than the individual properties of isolated graphene and nickel films.